Association of adverse childhood experiences with diabetes in adulthood: results of a cross-sectional epidemiological survey in Singapore. Issue 3 (15th March 2021) - Subramaniam, Mythily; Abdin, Edimansyah; Vaingankar, Janhavi Ajit; Chang, Sherilyn; Sambasivam, Rajeswari; Jeyagurunathan, Anitha; Seow, Lee Seng Esmond; Van Dam, Rob; Chow, Wai Leng; Chong, Siow Ann
Abstract : Objectives: Several studies have linked diabetes mellitus to adverse childhood experiences (ACEs). While a number of studies have examined the association between ACEs and diabetes in Western populations, few have done it in Asian populations. The current study aimed to examine (1) the association between ACEs and diabetes, including the association after age stratification, and (2) the association of comorbid depression, resource use and health-related quality of life (HRQoL) among those with diabetes and ACEs in Singapore. Settings: Participants were surveyed in their homes or any other preferred venue of their choice. Participants: 6126 individuals aged 18 years and above were randomly selected among Singapore residents. Design: Cross-sectional nationwide epidemiological study. Results: Exposure to any ACE was not associated with increased odds of diabetes; however, those who had experienced parental separation, death or divorce of a parent had higher odds of diabetes. In addition, we observed significant interaction between age and ACEs in relation to odds of diabetes. ACEs were significantly associated with higher odds of diabetes mainly in the younger age group. The prevalence of major depressive disorder was significantly higher among those with diabetes and ACEs than those with diabetes alone (3.7% and 0.3% respectively). Conclusions: Efforts to promote regular exercise and healthy lifestyles both in the population and among those with diabetes must continue for the prevention and management of diabetes. The findings emphasise the need to create more awareness of both the prevalence and impact of ACEs among those treating chronic diseases.